VIDEO DOKUMENTER PROFIL CERITA KOPI DARI GINTUNG SEBAGAI MEDIA PROMOSI RINTISAN DESA WISATA DALAM USAHA MENANGKAP PELUANG PASAR MELALUI SITUS YOUTUBE - widhi nugroho; Sapto Hudoyo (LP2MP3M, INSTITUT SENI INDONESIA SURAKARTA, 2019)
ABSTRACT Promotion, as one of the marketing management efforts will inevitably have to follow the standardization of the market. The increasing use of the internet with video content such as youtube, making promotional work more independent and economical in order to find the market. Potentially, Gintung, Binangun Village, District Karangkobar can be developed into one tourist destination village with coffee plantation as the main commod-ity. Observation of the subject by combining several disciplines as an approach can be done in a study. This is done considering that the research process of creating video documentary work requires several elements of approach that not only stop at one discipline, but some approaches can be used to support the creativity side in the process of creating video documentary work of this profile.